Indirect Control of Donor/Acceptor Interactions for Highly Efficient Space‐Confined Thermally Activated Delayed Fluorescence Emitters - Feng, Zi‐Qi; Yang, Sheng‐Yi; Kong, Fan‐Cheng; Qu, Yang‐Kun; Meng, Xin‐Yue; Yu, You‐Jun; Zhou, Dong‐Ying; Jiang, Zuo‐Quan; Liao, Liang‐Sheng (Advanced functional materials, 2023)
Conformational engineering is essential to further reinforce the luminescent properties of thermally activated delayed fluorescence (TADF) materials featuring through‐space charge transfer (TSCT) characteristics. Herein, two TSCT‐TADF emitters (8MeDM‐B and 8FDM‐B) with the methyl and fluorine moieties substituted at the C8 site of the rigid spiro‐fluorene bridge is reported. Derivation of the C8 site is first proposed to control the molecular configuration with the ability to indirectly tune the intramolecular interaction between donor and acceptor groups. As a result, 8MeDM‐B and 8FDM‐B both present small singlet‐triplet energy gaps, fast reverse intersystem crossing rates, and high photoluminescence quantum yields. Interestingly, the smaller fluorine atom not the bigger methyl group exhibits more evident electrostatic repulsive force onto the central donor and thus rectifies the central spiro structure. Consequently, the high external quantum efficiency values of 28.8% and 31.7% for 8MeDM‐B and 8FDM‐B‐based electroluminescence devices are achieved, respectively. This study offers a measure for enhancing TSCT‐TADF emitters without directly modifying the donor or acceptor. Two emitters, 8MeDM‐B and 8FDM‐B, have been synthesized with a methyl or fluorine group at the C8 site of the fluorene holder. Both emitters exhibit excellent performance in photoluminescence and electroluminescence, it is believed that this is a fine‐tuning method for TSCT‐TADF emitters based on another spatially neighboring position without directly modifying donor/acceptor segments.